Chinese medical teachers’ cultural attitudes influence palliative care education: a qualitative study - Willemsen, Antonia M. (BMC Palliat Care, 2021)
BACKGROUND: China holds one fifth of the world’s population and faces a rapidly aging society. In its ambition to reach a health care standard comparable to developed countries by 2030, the implementation of palliative care gains special importance. Until now, palliative care education in China is limited and disparate. This study aims to explore and determine factors that have impeded the development and implementation of palliative care education in China. METHODS: We conducted semi-structured interviews with n=28 medical teachers from seven Chinese universities. Interviews were transcribed, and thematic analysis applied. RESULTS: Three themes with two subthemes were constructed from data analysis. Theme 1 covers the still ambivalent perception of palliative care and palliative care education among participants. The second theme is about cultural attitudes around death and communication. The third theme reflects participants’ pragmatic general understanding of teaching. All themes incorporate obstacles to further implementation of palliative care and palliative care education in China. CONCLUSIONS: According to the study participants, palliative care implementation through palliative care education in China is hindered by cultural views of medical teachers, their perception of palliative care and palliative care education, and their understanding of teaching. The study demonstrates that current attitudes may work as an obstacle to the implementation of palliative care within the health care system. Approaches to changing medical teachers’ views on palliative care and palliative care education and their cultural attitudes towards death and dying are crucial to further promote the implementation of palliative care in China. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12904-020-00707-w.